ПЕДАГОГІЧНА ВЗАЄМОДІЯ ВЧИТЕЛЯ ТА УЧНІВ ЯК ЗАСІБ ФОРМУВАННЯ ТВОРЧОЇ ОСОБИСТОСТІ В ПРОЦЕСІ НАВЧАННЯ (Педагогіка вищої та середньої школи, 2001)
Pedagogical relationship between the teacher and pupils is a method of forming a creative personality in the process of studying.This article is talked about the peculiarities of forming the creative personality in the conditions of realizing the pedagogical relationship between the teacher and pupils. They analyze the influence of psychological development and demands of teenagers on the organized basis of creative relationships. The author stresses the contrasts between the theory of pedagogical relationship and real school life. The author tells about the necessary conditions for realizing the personality of a child and his self-determination in the process of studying.